2019
DOI: 10.1186/s12896-019-0561-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the GmRD26 soybean promoter in response to abiotic stresses: potential tool for biotechnological application

Abstract: BackgroundDrought is one of the most harmful abiotic stresses for plants, leading to reduced productivity of several economically important crops and, consequently, considerable losses in the agricultural sector. When plants are exposed to stressful conditions, such as drought and high salinity, they modulate the expression of genes that lead to developmental, biochemical, and physiological changes, which help to overcome the deleterious effects of adverse circumstances. Thus, the search for new specific gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…However, the regulation of the drought response in soybean remains poorly understood. It was reported that overexpressing the orthologues of Arabidopsis ABA‐responsive genes in soybean, such as GmMYB84 , GmWRKY12 , GmWRKY54 and GmRD26 , could enhance ABA signaling and confer drought tolerance (Wang et al ., 2017; Shi et al ., 2018; Freitas et al ., 2019; Wei et al ., 2019). However, these regulations usually occurred in the downstream position, particularly on downstream transcriptional factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the regulation of the drought response in soybean remains poorly understood. It was reported that overexpressing the orthologues of Arabidopsis ABA‐responsive genes in soybean, such as GmMYB84 , GmWRKY12 , GmWRKY54 and GmRD26 , could enhance ABA signaling and confer drought tolerance (Wang et al ., 2017; Shi et al ., 2018; Freitas et al ., 2019; Wei et al ., 2019). However, these regulations usually occurred in the downstream position, particularly on downstream transcriptional factors.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of promoters help to understand the specificity mechanism of plant genes responding to abiotic stresses. For example, the GmRD26 (a NAC transcription factor) promoter has been characterized as being involved in stress and ABA response; ABRE motifs and ABA responsive elements were thought to be the key factor influencing the stress-responsive gene expression regulated by GmRD26 under drought stress [ 39 ]. In transgenic tobacco, disruption of an E-box/ABRE-like motif in the storage protein napA promoter led to the complete abolishment of reporter gene expression, suggesting that E-box is a core motif conferring napA promoter activity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total proteins of transgenic soybean root nodules were extracted and quantified as previously described (Freitas et al, 2019). GUS assay was performed in a mixture containing 10 mM of 4-methylumbelliferyl-β-D-glucuronide (MUG; Sigma, United States), and the mixture was incubated for 1 h at 37 • C. The fluorescence product of 4-methylumbelliferone (4-MU) was monitored using a VersaFluor Fluorometer (Bio-Rad) with excitation at 365 nm and emission at 455 nm.…”
Section: Gus Activity Assaymentioning
confidence: 99%